2017
DOI: 10.5539/ibr.v10n8p129
|View full text |Cite
|
Sign up to set email alerts
|

Wi-Fi Adoption and Security in Hong Kong

Abstract: The benefit of using WiFi for Internet connection is obvious: cost-effective and powerful. WiFi gives us the flexibility and convenience of not being tied to a fixed location. Nowadays, more and more electronic devices and gadgets, such as mobile phones, cameras, gaming devices, TV and entertainment equipment, are WiFi enabled. WiFi also enables your devices to share files instantly. WiFi broadcasting devices, such as Chromecast, give you extra convenience by allowing you to stream video and audio contents fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…In the city of Rabat, the capital of Morocco, it was identi ed, among other aspects, that 10% of Wi-Fi networks used WEP (Wired Equivalent Privacy) as a network security protocol (Sebbar et al 2016). A Similar percentage to the identi ed in Hong Kong, where it was observed that about 7% of the analyzed networks used the same security protocol (Fong and Wong 2016).…”
Section: Introductionsupporting
confidence: 78%
“…In the city of Rabat, the capital of Morocco, it was identi ed, among other aspects, that 10% of Wi-Fi networks used WEP (Wired Equivalent Privacy) as a network security protocol (Sebbar et al 2016). A Similar percentage to the identi ed in Hong Kong, where it was observed that about 7% of the analyzed networks used the same security protocol (Fong and Wong 2016).…”
Section: Introductionsupporting
confidence: 78%
“…In the last few decades, as we were witnessing the emergence of the "information age" and the third industrial revolution, wireless access and localization played an undisputable role by enabling millions of innovative and popular cyberspace applications to connect to the Internet by anyone, anywhere 1 . These cyberspace applications have had and continue to make a fundamental impact on the way we live, conduct business, shop, access news media, deliver education, transport, care for health, and interact with the world.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to smartphones, many other devices like home entertainment systems, environmental monitoring sensors, and security systems connect to the Internet with Wi-Fi, but not necessarily through cellular networks. Wi-Fi brings people, processes, data, and devices, together and turns data into valuable information that makes life better and business thrive [1]. Some companies engaged in Wi-Fi related business resort to artistic illustrations similar to Fig.…”
Section: Introductionmentioning
confidence: 99%